2005
DOI: 10.1369/jhc.4a6474.2005
|View full text |Cite
|
Sign up to set email alerts
|

Muscular ETBReceptors Develop Postnatally and Are Differentially Distributed in Specific Segments of the Rat Vasculature

Abstract: S U M M A R YThe endothelin/endothelin-receptor system is a key player in the regulation of vascular tone in mammals. We raised and characterized an antiserum against rat ET B receptor and investigated the distribution of ET B receptors in different vascular beds during postnatal development (day 0 through day 28) and in the adult rat. We report the tissuespecific and age-dependent presence of vasoconstrictor ET B receptors. At the time of birth, vascular smooth muscle cells from all tissues examined did not e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
1
10
1
Order By: Relevance
“…Such was also the case in membrane studies of both rat and rabbit renal microvessels, which showed that ET A R and ET B R are present in a proportion of 40:60 (5). Studies of the expression of ET B R in the neonatal rat kidney demonstrate that, by day 28 after birth, the interlobar artery develops immunofluorescent staining for ET B R (37). Interestingly, in this study, the main renal artery (as well as mesenteric and pulmonary arteries) was devoid of staining for ET B R, which suggests that conduit vessels express only ET A R (37).…”
contrasting
confidence: 42%
“…Such was also the case in membrane studies of both rat and rabbit renal microvessels, which showed that ET A R and ET B R are present in a proportion of 40:60 (5). Studies of the expression of ET B R in the neonatal rat kidney demonstrate that, by day 28 after birth, the interlobar artery develops immunofluorescent staining for ET B R (37). Interestingly, in this study, the main renal artery (as well as mesenteric and pulmonary arteries) was devoid of staining for ET B R, which suggests that conduit vessels express only ET A R (37).…”
contrasting
confidence: 42%
“…However, since the S6c-mediated vasoconstriction after 7 h incubation was not completely abolished in presence of U0126, this initial functional upregulation might involve additional mechanisms. Studies have shown that even fresh coronary arteries from healthy rats contain ET B receptor protein in VSMC (Wendel-Wellner et al 2002;Wendel et al 2005). Hence, we speculate that a part of the contractile ET B receptor upregulation may involve post-translational modifications of already expressed ET B receptors.…”
Section: Discussionmentioning
confidence: 78%
“…13,17,20,31,47,58 Exogenous administration of ET-1 evokes severe pain that is associated with allodynia in the injected limb in humans and spontaneous painassociated behaviors and allodynia/hyperalgesia in rodents. 12,14,34 With the increased recognition of developmental differences in pain and analgesia 21 and evidence that ET receptor expression changes with maturation and sex in a number of tissues, 1,27,41,56 we hypothesize that ET-1-induced nociception may be age-and sex-dependent. Male and female rats of 3 ages have been included: Postnatal day 7, 21, and 60 rats that model human infant, child, and young adult, respectively.…”
mentioning
confidence: 98%